Digitisation education in Hungary - Koltay, Tibor (Knjižnica, 2012)
Purpose: the paper aims to present experience in digitisation education at the Hungarian school of library and information science and to indicate various problematic issues and challenges that have arisen. To overcome a part of these problems it is userful to rely on the experience of similar digitisation projects and education programmes in Hungary and abroad. Methodology/approach: besides presenting the digitisation education programme at the Szent István university in Jászberény, a review of digitisation projects and digital libraries is given. Details about Hungarian digital resources are provided. Results: seven-year experience in the project-based digitisation education incorporated in the LIS programme at the Szent István university, Hungary shows many similarities with courses and programs offered by other European universities. The most serious challenge is to make the education based on real-life tasks. Research limitation: the results of one type of coursework have been studied. Originality/practical implications: building a digital library in a small country encounters the same problems as the one presented in the study which puts digitisation into acontext, comparable to other European projects.
Keywords: visokošolski študij; študijski programi; library science; bibliotekarstvo; digitalizacija; digitization; Hungary; Madžarska